2006
DOI: 10.1111/j.1742-4658.2006.05544.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase ε associates with the elongating form of RNA polymerase II and nascent transcripts

Abstract: RNA polymerase II (RNA pol II) transcribes proteinencoding genes in eukaryotes. It can be purified as a 'core' enzyme containing 10-12 subunits with a molecular mass of 500 kDa. However, larger RNA pol II-containing complexes, capable of transcribing from model promoters in vitro with minimal addition of general transcription factors, have also been purified [1]. These 'holoenzyme' complexes contain general transcription factors, other transcriptional mediators, as well as various sets of accessory proteins, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 72 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…Double staining used 5-and 10-nm gold particles to label Bet v 1 and caveolin 2, respectively (see the Methods section in this article's Online Repository). 18 Specimens from 3 allergic and 3 healthy subjects were analyzed.…”
Section: Immunotransmission Emmentioning
confidence: 99%
“…Double staining used 5-and 10-nm gold particles to label Bet v 1 and caveolin 2, respectively (see the Methods section in this article's Online Repository). 18 Specimens from 3 allergic and 3 healthy subjects were analyzed.…”
Section: Immunotransmission Emmentioning
confidence: 99%
“…The seven genes relatively up-regulated within the refractory cohort (Table IV) included RABGGTB, encoding a prenyl transeferase with anti-apoptotic properties, and POLE, involved in DNA replication and repair (Miura & Izuta, 2004;Rytkonen et al, 2006).…”
Section: Gene Biologymentioning
confidence: 99%
“…Moreover, ChIP analysis has revealed that RNAP-II complexes bound to the rDNA locus contain Ser7P-CTD and hypophosphorylated RNAP-II molecules (Figure S3). Different studies have demonstrated that the CTD of RNAP-II interacts with several replication components, such as MCMs and DNA polymerase ε [54], [55]. However, the presence of DNA repair, replication or recombination factors in purified CTD-RNAP-II has been found to depend strongly on the purification strategy employed [54], [56], [57].…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have demonstrated that the CTD of RNAP-II interacts with several replication components, such as MCMs and DNA polymerase ε [54], [55]. However, the presence of DNA repair, replication or recombination factors in purified CTD-RNAP-II has been found to depend strongly on the purification strategy employed [54], [56], [57]. The results presented herein suggest that hypophosphorylated RNAP-II and Ser2P-CTD RNAP-II complexes, but not Ser5P-CTD, interact with Orc1p (Figure 5).…”
Section: Discussionmentioning
confidence: 99%